Performance Analysis of Matrix Pencil Method Applied to High-Resolution Measurement of Supraharmonics - Kaite Li; Wei Zhao; Shisong Li; Songling Huang (Energies, 2023)
Supraharmonics emitted by power electronic equipment will cause electromagnetic interference. However, there is no uniform standard for the measurement of supraharmonics. Unlike non-parametric methods, such as Fourier transform, the matrix pencil method has attracted the attention of researchers in many fields because of its super-resolution characteristics. In this paper, an attempt is made to apply the matrix pencil method to the high-resolution measurement of supraharmonics. Noting that parametric methods offer a promising alternative strategy for high time-resolution analysis of supraharmonics, the matrix pencil method is introduced for high-resolution measurements and estimating the supraharmonic components in grid voltage and current signals. By deriving and analyzing the Cramér–Rao bound of the method, two excellent properties of the matrix pencil method are found: robustness to time-varying signals in supraharmonics measurements and accuracy in frequency localization of components with large amplitudes. Meanwhile, the effectiveness of the matrix pencil method when applied to the high-resolution estimation and measurement of supraharmonics in grid signals is demonstrated by measuring, estimating, and analyzing grid voltage and current signals containing different typical supraharmonics characteristics. This parametric approach opens up a new avenue that allows more signal information to be obtained while maintaining high accuracy, thus enabling the analysis of supraharmonics with higher time resolution.